Beclin‐1 improves mitochondria‐associated membranes in the heart during endotoxemia - Sun, Yuxiao (FASEB Bioadv, 2021)
Mitochondria‐associated membranes (MAMs) are essential to mitochondria. This study was to determine whether endotoxemia rearranges MAMs in the heart, and whether Beclin‐1 regulates this process. Wild‐type mice and mice with a cardiac‐specific overexpression of Beclin‐1 (Becn1‐Tg), or a heterozygous knockout of Beclin‐1 (Becn1 (+/−)) were given lipopolysaccharide (LPS) challenge. In the heart, the ultrastructure of MAMs was examined by electron microscopy and the histology evaluated by immunostaining. Additionally, MAMs were isolated by ultracentrifugation, and their content and function were quantified. The effects of Beclin‐1‐activating peptide (TB‐peptide) on MAMs were also examined. Data showed that endotoxemia decreased both the total mass and the function of MAMs, and these deficiencies became worse in Becn1 (+/−) mice but were alleviated in Becn1‐Tg and TB‐peptide‐treated mice. Responses of myocardial MAMs to LPS and to TB‐peptide were additionally examined in AC16 human cardiomyocytes. In vitro findings recaptured the effects of LPS and TB‐peptide in cardiomyocytes; the challenge of LPS reduced the level and activity of MAMs, and TB‐peptide attenuated this defect. Together, the results suggest a new function of Beclin‐1 in improving cardiac MAMs during endotoxemia, providing a mechanism for the previously identified role of Beclin‐1 in protection of mitochondria and cardiac function.